On the Transmission of Colour Image Over Double Generalized Gamma FSO Channel - N. Ilic, Milos; P. Prlincevic, Bojan; C. Spalevic, Petar; R. Panic, Stefan; D. Drajic, Dejan (Elektronika ir Elektrotechnika, 2017)
In this paper performance analysis of colour image Free Space Optics (FSO) transmission over Double Generalized Gamma (DGG) turbulence communication channel is carried out. At the reception side, we have used an average bit error rate (ABER) for reconstructed image performance measure, as the function of FSO link transmission parameters, such as propagation distance, Rytov variance and turbulence shaping and severity parameters (γ1, γ2, m1, m2). Obtained results cover a large number of colour image FSO transmission scenarios, for Gamma-Gamma, Double-Weibull and K turbulence models channels considered as special cases. DOI: http://dx.doi.org/10.5755/j01.eie.23.2.18004